Элементы нелинейного анализа информационных потоков - Грайворонская, А.Н.; Ландэ, Д.В. (Реєстрація, зберігання і обробка даних, 2017)
Рассмотрены методы нелинейной динамики, которые применяются для анализа временных рядов, соответствующих информационным потокам в сети Интернет. Большинство из этих методов базируются на корреляционном, фрактальном, мулътифракталъном, вейвлет- и Фуръе-анализе. Детально описаны особенности этих методов, их взаимосвязь. Представленные методы и соответствующие алгоритмы могут быть использованы для выявления особенностей в динамике развития информационных процессов, выявления периодичностей, аномалий, свойств самоподобия, а также взаимной коррелированности и прогнозирования развития различных информационных процессов. Представленные методы могут быть рассмотрены как основа для выявления информационных атак, кампаний, операций, войн. Розглянуто методи нелінійної динаміки, які застосовуються для аналізу часових рядів, що відповідають інформаційним потокам у мережі Інтернет. Більшість із цих методів базуються на кореляційному, фрактальному, мультифрактальному, вейвлет- і Фур’є-аналізі. Детально описано особливості цих методів, їхній взаємозв’язок. Представлені методи та відповідні алгоритми можуть використовуватися для виявлення особливостей у динаміці розвитку інформаційних процесів, виявлення періодичності, аномалій, властивостей самоподібності, а також взаємної корельованості тапрогнозування розвитку різних інформаційних процесів. Представлені методи можуть розглядатись як основа для виявлення інформаційних атак, кампаній, операцій, війн. The methods of nonlinear dynamics to apply for analysis of time series corresponding to information streams on the Internet are considered. The information stream consists of documents published on the Internet during some time and related to a certain topic. If one gathers such documents with time stamps, then it is possible to define the time series as the amounts of documents published in short periods and analyze how these amounts vary over time. In the main, the methods discussed are based on correlation, fractal, multifractal, wavelet, and Fourier analysis. The article is dedicated to a detailed description of these approaches and interconnections among them. For instance, correlation is a concept of particular importance and a basis for many techniques. On the other hand, information processes are often self-similar; therefore, fractal and multifractal analysis can provide insights into structure and properties of such processes. The methods and corresponding algorithms presented can be used for detecting key points in the dynamic of information processes; identifying periodicity, anomaly, self-similarity, and correlations; forecasting various information processes. The methods discussed can form the basis for detecting information attacks, campaigns, operations, and wars.